Symbiont retention and holobiont response under simulated sulfide deprivation in Lucinid clams from seagrass beds - Orgeas-Gobin, Samuel; Piquet, Bérénice; Marie, Benjamin; Andersen, Ann C.; Tanguy, Arnaud; Duperron, Sébastien (Frontiers in Microbiology, 2025)
Bivalves of the family Lucinidae thrive in sulfidic sediments thanks to their chemoautotrophic bacterial symbionts. However, how different Lucinidae species respond to sulfide deprivation and associated symbiont loss remains poorly understood. Here, we investigated the responses of Lucinoma borealis and Loripes orbiculatus, two species that co-occur in temperate seagrass beds, exposed to prolonged sulfide starvation. Using metabolomics, ultrastructural TEM analyses and 16S rRNA-based metabarcoding, we monitored and compared responses in gills and visceral mass over a 4-month period. Both host species as well as their symbionts survived sulfide-free conditions. Hosts tissues displayed limited impact on ultrastructure and metabolites. Despite decrease in numbers and activity level, symbionts remained present throughout the experiment and no evidence for bacteremia or infection was detected. Our results also revealed differences, in particular in host apoptosis response, suggesting species-specific stress strategies. Altogether, both holobionts can survive extended low-sulfide periods without critical damage and without completely losing their symbionts. These could be adaptations to the extended low-sulfide periods that are associated with low primary production and the cold season in seagrass beds. Adaptations could involve a switch in the symbionts' physiological state to preserve a dormant symbiotic population. These findings highlight the importance of stress tolerance mechanisms in coastal Lucinidae, and raise questions about the nature of host–symbiont dependency in these periods.